El matrimonio y la unión de hecho como bases primordiales del núcleo familiar en el Ecuador: nuevo análisis - Andrade Alban, Sabrina Vanessa (2019)
Marriage and de facto unions as primary foundation of the family unit in Ecuador. New is a research project aimed at routing and check what happens with these two transcendental figures right, its origin and beginning in history, its development, utility and use in Ecuador and its current status in it. Living in complete and utter discrimination, Gbtl, community have demanded categorically that they recognize the same rights as heterosexual people, claiming to include gay marriage in the Ecuadorian legislation, as has happened in several legislation worldwide….